If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 + n = -52 Solving -22 + n = -52 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + n = -52 + 22 Combine like terms: -22 + 22 = 0 0 + n = -52 + 22 n = -52 + 22 Combine like terms: -52 + 22 = -30 n = -30 Simplifying n = -30
| 5X+4=76 | | (25/64)^(-1/2) | | 3x^2-11x-20x=0 | | -4x^2+36x+40=0 | | -100+15= | | 5/2.5=x/7.5 | | -29=6+5w | | 25-(x-7)=9x-2 | | 0=x^2-13x+42.25 | | (25/64)^-1/2 | | 6x-12=-9x | | 49=6b+9+2b | | (4x+8)(x+4)=480 | | v-17v=-6 | | 2x+2x=15 | | 3/7=z/63 | | 32.5p=260.0 | | 17/26=w/52 | | (-6x+-2)=-32-x | | 0-(-43)= | | e^3x-1=10 | | 3k+4k=12 | | 2x+3+4=7x+2x-14 | | 39/54=d/18 | | [b/5]=1 | | 32=4-4w | | 4x+6+3x=41 | | -8+x+5-7=20x-10 | | 27.50x+17=23.25x+17 | | 5(4x-3)+8=2 | | 6x+3=-2+11 | | (X-8y+2)*(3x-2c+100)=0 |